Optimizing methods to study host cell signaling responses upon receptor docking of Clostridioides difficile binary toxin - Barsk, Amanda (My University, 2025)
Clostridioides difficile infection (CDI), an urgent threat to human health, is caused by the Clostridioides difficile bacterium that produces TcdA and TcdB toxins. Some strains additionally produce C. difficile binary toxin (CDT), which is thought to increase the bacterium’s virulence. The CDT toxin has two subunits, CDTa (enzymatic subunit) and CDTb (cell binding subunit). CDTb docks to the lipolysis-stimulated lipoprotein receptor (LSR), enabling CDTa endocytosis, but it also has CDTa-independent functions, that are poorly known on the molecular level. Identification of LSR interacting proteins upon CDTb binding is expected to advance the molecular understanding of CDI. Protein interactions can be studied with proximity dependent biotinylation methods combined with mass spectrometry (proximity labeling-MS). This thesis aimed to optimize methods for proximity labeling-MS to identify proteins interacting with LSR after CDTb docking. Experimental objectives included the following: Elucidation of protein characteristics of LSR and CDTb utilizing in silico tools. Transfection of cells to achieve MAC-tagged LSR expression. Simulation of canonical oligomerization of CDTb via trypsinization. Verification of interaction between LSR-MAC and CDTb on the plasma membrane of cells. Experiments were conducted on Human Embryonic Kidney cells (HEK293T). The semi-stable expression of LSR-MAC partly on the plasma membrane was confirmed by cell fractionation, western blot, and confocal microscopy. Oligomerization of CDTb via trypsinization was confirmed with Size Exclusion Chromatography-Multi Angle light scattering (SEC-MALS). CDTb and LSR-MAC interaction was confirmed with flow cytometry. These optimized methods will enable utilization of proximity labeling-MS to study intracellular protein interactions following CDTb toxin docking to LSR.

Clostridioides difficile infektiota (CDI), joka on uhka ihmisterveydelle, aiheuttaa Clostridioides difficile bakteeri tuottamillaan TcdA ja TcdB toksiineilla. Jotkut kannat tuottavat lisäksi C. difficile binaaritoksiinia (CDT), jonka uskotaan lisäävän bakteerin virulenssia. CDT toksiinissa on kaksi alayksikköä, CDTa (entsymaattinen yksikkö) ja CDTb (soluun sitoutuva yksikkö). CDTb sitoutuu lipolyysis-stimuloituun lipoproteiini reseptoriin (LSR) mahdollistaen CDTa:n endosytoosin, mutta CDTb:llä on myös itsenäsisiä funktioita, jotka tunnetaan heikosti molekyylitasolla. CDTb:n sitoutuessa LSR:ään, reseptorin kanssa interaktoivien proteiinien tunnistamisen uskotaan edistävän molekyylistä ymmärrystä CDI:stä. Proteiini interaktioita voidaan tutkia proksimiteetti riippuvaisilla biotinylaatio metodeilla yhdistettynä massaspektrometriaan (proksimitetti merkitseminen-MS). Tämä turkielma pyrki optimoimaan metodeja proksimiteetti merkitseminen-MS:ää varten, jotta LSR:n kanssa interaktoivat proteiinit CDTb:n sitoutumisen yhteydessä voitaisiin tunnistaa. Kokeelliset tavoitteet olivat seuraavat: 1) LSR ja CDTb proteiinien ominaisuuksien selvittäminen hyödyntäen in silico työkaluja, 2) solujen transfektointi saavuttaaksemme MAC-tägätyn LSR:n ekspression, 3) kanonisen CDTb oligomerisaation simulointi trypsinisaatiolla, ja 4) LSR-MAC:in ja CDTb:n välisen interaktion varmistaminen solujen plasma membraanilla. Kokeet suoritettiin Human Embryonic Kidney –soluilla (HEK293T). LSR-MAC:in semi-stabiili ekspressio osaksi solujen plasma membraanilla varmistettiin solufraktioinilla, western blotilla, ja konfokaali mikroskopialla. CDTb:n oligomerisaatio trypsinoinilla varmistettiin size exclusion chromatography-multi angle light scattering (SEC-MALS) –metodilla. CDTb ja LSR-MAC interaktio varmistettiin flow cytometrialla. Nämä optimoidut metodit tulevat mahdollistamaan proksimiteetti merkisteminen-MS:n hyödyntämisen solunsisäisten proteiini interaktioiden tutkimiseksi CDTb toksiinin sitoutuessa LSR reseptoriin.
Keywords: C. difficile, CDT, LSR, proximity labeling-MS